Is Decreased Xylem Sap Surface Tension Associated With Embolism and Loss of Xylem Hydraulic Conductivity in Pathogen-Infected Norway Spruce Saplings? - Paljakka, Teemu; Rissanen, Kaisa; Vanhatalo, Anni; Salmon, Yann; Jyske, Tuula; Prisle, Nønne L.; Linnakoski, Riikka; Lin, Jack J.; Laakso, Tapio; Kasanen, Risto; Bäck, Jaana; Hölttä, Teemu (Frontiers in Plant Science, 2020)
Increased abiotic stress along with increasing temperatures, dry periods and forest disturbances may favor biotic stressors such as simultaneous invasion of bark beetle and ophiostomatoid fungi. It is not fully understood how tree desiccation is associated with colonization of sapwood by fungi. A decrease in xylem sap surface tension (σxylem) as a result of infection has been hypothesized to cause xylem embolism by lowering the threshold for air-seeding at the pits between conduits and disruptions in tree water transport. However, this hypothesis has not yet been tested. We investigated tree water relations by measuring the stem xylem hydraulic conductivity (Kstem), σxylem, stem relative water content (RWCstem) and water potential (Ψstem), and canopy conductance (gcanopy), as well as the compound composition in xylem sap in Norway spruce (Picea abies) saplings. We conducted our measurements at the later stage of Endoconidiophora polonica infection when visible symptoms had occurred in xylem. Saplings of two clones (44 trees altogether) were allocated to treatments of inoculated, wounded control and intact control trees in a greenhouse. The saplings were destructively sampled every second week during summer 2016. σxylem, Kstem and RWCstem decreased following the inoculation, which may indicate that decreased σxylem resulted in increased embolism. gcanopy did not differ between treatments indicating that stomata responded to Ψstem rather than to embolism formation. Concentrations of quinic acid, myo-inositol, sucrose and alkylphenol increased in the xylem sap of inoculated trees. Myo-inositol concentrations also correlated negatively with σxylem and Kstem. Our study is a preliminary investigation of the role of σxylem in E. polonica infected trees based on previous hypotheses. The results suggest that E. polonica infection can lead to a simultaneous decrease in xylem sap surface tension and a decline in tree hydraulic conductivity, thus hampering tree water transport.